Loji nuklear jamin bekalan sumber tenaga - Alang Md Rashid, Nahrul Khair (Berita Harian, 2011)
This is an interview with journalists from Berita Minggu, a national Malay Language newspaper following the Fukushima nuclear reactor accident.